ARCHETYPE OF TRANSFORMATION IN THE LEGEND OF SLEEPERS BY DANILO KIŠ (Heritage, 2024)
Considering that the mythical subtext of the novelette 'The Legend of Sleepers' from the collection The Encyclopedia of the Dead by Danilo Kiš has not been sufficiently analyzed in literary science, this paper deals with intertextual relations which this text has with the holy books – the Quran, the Talmud and the Bible. Special attention is given to the main motifs of death and resurrection, reviewing the temporal and spatial framework of narration. It is stressed that the period of dreaming is very long and that the cave is a secretive locus, which corresponds with the metamorphoses of the characters on symbolic level, as well as with their unconscious state during the separation of the spiritual from the physical part of the sleeping being. Мethodological approach lies in Carl Gustav Jung's archetypal theory. Conclusions are made through the text analyses with the review of its paratextual elements – motto of the collection, motto of the novelette, writer’s notes at the end of the book. The research results indicate that the author reinterprets the myth and questions the sources he relies on because he treats them with irony.
Keywords: Danilo Kiš, 'The Legend of Sleepers', holy books, mythical subtext, archetype, transformation, cave